2023
DOI: 10.1111/cod.14481
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of metal allergy to the failure of metal alloy implants, with special reference to titanium: Current knowledge and controversies

Chenghao Huang,
Shu Yu Vanessa Chiang,
David J. Gawkrodger

Abstract: After almost three‐quarters of a century during which contact dermatologists have often struggled to comprehend the relationship between metal allergy and failure of metal‐alloy containing implant, it is possible to say that a relationship does exist, particularly for cobalt and chromium, but also for nickel. There is still debate as to whether allergy develops as a consequent of failure but thenceforth contributes to it, or whether sensitisation starts first and induces failure secondarily—opinion probably fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 108 publications
0
0
0
Order By: Relevance
“…Commercially pure titanium, denoted as α-Ti, finds extensive application in biomedicine (including orthopedic implants and dental instruments), as well as in aerospace engineering [2]. This popularity stems from its remarkable properties, including excellent fatigue strength, low density, high tensile strength, lightweight nature, exceptional biocompatibility, and outstanding resistance to corrosion [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially pure titanium, denoted as α-Ti, finds extensive application in biomedicine (including orthopedic implants and dental instruments), as well as in aerospace engineering [2]. This popularity stems from its remarkable properties, including excellent fatigue strength, low density, high tensile strength, lightweight nature, exceptional biocompatibility, and outstanding resistance to corrosion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the corrosion of surgical Ti implants, a significant determinant of their service life, cannot ensure their long-term stability [4]. This corrosion process compromises the chemical and physical stability of the surface, potentially leading to various side effects [3]. For instance, Olmedo et al have demonstrated an association between per-implantitis (a site-specific infectious disease) and ion corrosion of the Ti surface [5].…”
Section: Introductionmentioning
confidence: 99%